Respuestas
Respuesta dada por:
0
(1) Tratemos de hacer un cambio de variable para ver mejor la cosa
![x=zy\to dx=z~dy+y~dz x=zy\to dx=z~dy+y~dz](https://tex.z-dn.net/?f=x%3Dzy%5Cto+dx%3Dz%7Edy%2By%7Edz)
(2) Ahora reemplacemos
![y^3(z^3-1)(z~dy+y~dz)+3zy^3~dy=0\\ \\
(z^3-1)(z~dy+y~dz)+3z~dy=0\\ \\
(z^3-1)z~dy+(z^3-1)y~dz+3z~dy=0\\ \\
(z^3+2)zdy+(z^3-1)y~dz=0\\ \\
\dfrac{dy}{y}+\dfrac{z^3-1}{z(z^3+2)}~dz=0 y^3(z^3-1)(z~dy+y~dz)+3zy^3~dy=0\\ \\
(z^3-1)(z~dy+y~dz)+3z~dy=0\\ \\
(z^3-1)z~dy+(z^3-1)y~dz+3z~dy=0\\ \\
(z^3+2)zdy+(z^3-1)y~dz=0\\ \\
\dfrac{dy}{y}+\dfrac{z^3-1}{z(z^3+2)}~dz=0](https://tex.z-dn.net/?f=y%5E3%28z%5E3-1%29%28z%7Edy%2By%7Edz%29%2B3zy%5E3%7Edy%3D0%5C%5C+%5C%5C%0A%28z%5E3-1%29%28z%7Edy%2By%7Edz%29%2B3z%7Edy%3D0%5C%5C+%5C%5C%0A%28z%5E3-1%29z%7Edy%2B%28z%5E3-1%29y%7Edz%2B3z%7Edy%3D0%5C%5C+%5C%5C%0A%28z%5E3%2B2%29zdy%2B%28z%5E3-1%29y%7Edz%3D0%5C%5C+%5C%5C%0A%5Cdfrac%7Bdy%7D%7By%7D%2B%5Cdfrac%7Bz%5E3-1%7D%7Bz%28z%5E3%2B2%29%7D%7Edz%3D0)
(3) resolvamos
![\displaystyle
\int\dfrac{dy}{y}+\int\dfrac{z^3-1}{z(z^3+2)}~dz=C\\ \\ \\
\ln|y|+\int\dfrac{3z^2}{2(z^3+2)}-\dfrac{1}{2z}~dz=C\\ \\ \\
\ln|y|+\dfrac{3}{2}\int\dfrac{z^2}{z^3+2}dz-\dfrac{1}{2}\int\dfrac{1}{z}~dz=C\\ \\ \\
\ln|y|+\dfrac{1}{2}\int\dfrac{d(z^3+2)}{z^3+2}dz-\dfrac{1}{2}\ln|z|=C\\ \\ \\
\ln|y|+\dfrac{1}{2}\ln|z^3+2|-\dfrac{1}{2}\ln|z|=C\\ \\ \\
\ln|y|+\ln\left|\dfrac{\sqrt{z^3+2}}{\sqrt{z}}\right|=C\\ \\ \\
\ln\left|\dfrac{y\sqrt{z^3+2}}{\sqrt{z}}\right|=C\\ \\ \\
\displaystyle
\int\dfrac{dy}{y}+\int\dfrac{z^3-1}{z(z^3+2)}~dz=C\\ \\ \\
\ln|y|+\int\dfrac{3z^2}{2(z^3+2)}-\dfrac{1}{2z}~dz=C\\ \\ \\
\ln|y|+\dfrac{3}{2}\int\dfrac{z^2}{z^3+2}dz-\dfrac{1}{2}\int\dfrac{1}{z}~dz=C\\ \\ \\
\ln|y|+\dfrac{1}{2}\int\dfrac{d(z^3+2)}{z^3+2}dz-\dfrac{1}{2}\ln|z|=C\\ \\ \\
\ln|y|+\dfrac{1}{2}\ln|z^3+2|-\dfrac{1}{2}\ln|z|=C\\ \\ \\
\ln|y|+\ln\left|\dfrac{\sqrt{z^3+2}}{\sqrt{z}}\right|=C\\ \\ \\
\ln\left|\dfrac{y\sqrt{z^3+2}}{\sqrt{z}}\right|=C\\ \\ \\](https://tex.z-dn.net/?f=%5Cdisplaystyle%0A%5Cint%5Cdfrac%7Bdy%7D%7By%7D%2B%5Cint%5Cdfrac%7Bz%5E3-1%7D%7Bz%28z%5E3%2B2%29%7D%7Edz%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%7Cy%7C%2B%5Cint%5Cdfrac%7B3z%5E2%7D%7B2%28z%5E3%2B2%29%7D-%5Cdfrac%7B1%7D%7B2z%7D%7Edz%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%7Cy%7C%2B%5Cdfrac%7B3%7D%7B2%7D%5Cint%5Cdfrac%7Bz%5E2%7D%7Bz%5E3%2B2%7Ddz-%5Cdfrac%7B1%7D%7B2%7D%5Cint%5Cdfrac%7B1%7D%7Bz%7D%7Edz%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%7Cy%7C%2B%5Cdfrac%7B1%7D%7B2%7D%5Cint%5Cdfrac%7Bd%28z%5E3%2B2%29%7D%7Bz%5E3%2B2%7Ddz-%5Cdfrac%7B1%7D%7B2%7D%5Cln%7Cz%7C%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%7Cy%7C%2B%5Cdfrac%7B1%7D%7B2%7D%5Cln%7Cz%5E3%2B2%7C-%5Cdfrac%7B1%7D%7B2%7D%5Cln%7Cz%7C%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%7Cy%7C%2B%5Cln%5Cleft%7C%5Cdfrac%7B%5Csqrt%7Bz%5E3%2B2%7D%7D%7B%5Csqrt%7Bz%7D%7D%5Cright%7C%3DC%5C%5C+%5C%5C+%5C%5C%0A%5Cln%5Cleft%7C%5Cdfrac%7By%5Csqrt%7Bz%5E3%2B2%7D%7D%7B%5Csqrt%7Bz%7D%7D%5Cright%7C%3DC%5C%5C+%5C%5C+%5C%5C%0A%0A)
![\dfrac{y\sqrt{z^3+2}}{\sqrt{z}}=e^C=K\\ \\ \\
\texttt{Resustituyendo variable: }z=\dfrac{x}{y}\\ \\ \\
\dfrac{x^3+2y^3}{x}=C_1 \dfrac{y\sqrt{z^3+2}}{\sqrt{z}}=e^C=K\\ \\ \\
\texttt{Resustituyendo variable: }z=\dfrac{x}{y}\\ \\ \\
\dfrac{x^3+2y^3}{x}=C_1](https://tex.z-dn.net/?f=%5Cdfrac%7By%5Csqrt%7Bz%5E3%2B2%7D%7D%7B%5Csqrt%7Bz%7D%7D%3De%5EC%3DK%5C%5C+%5C%5C+%5C%5C%0A%5Ctexttt%7BResustituyendo+variable%3A+%7Dz%3D%5Cdfrac%7Bx%7D%7By%7D%5C%5C+%5C%5C+%5C%5C%0A%5Cdfrac%7Bx%5E3%2B2y%5E3%7D%7Bx%7D%3DC_1)
(2) Ahora reemplacemos
(3) resolvamos
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años